Effect of Effective Microorganisms (EM1®) on Microflora Population and Carcass Yield of Quails - Jasmin Ahmad Sanusi, Nur-Sara; Ismail, Norshida; Afiza Badaluddin, Noor; Suhaili, Zarizal; Kamarudin, Ahmad-Syazni (International Journal of Engineering and Technology, 2018)
A total of 240 day-old Japanese quails were used to investigate the effect of EM1® on the microflora population and carcass quality of the quails in day 42 through drinking water. They were assigned randomly into four groups with 60 quails per treatments. The four treatments groups were given drinking water (DW) supplemented with EM1® (EM) with different rations which were: i) Drinking water (control group), ii) 1L EM + 250mL DW, iii) 1L EM + 500 mL DW and, iv) 1L EM + 750 mL DW. The result shows the population of Escherichia coli in the jejunum and faeces of the quails decrease significantly (p
Keywords: Effective Microorganism (EM1Â®); Coturnix japonica; Gut Microflora; Carcass Quality.